The Cognitive Turn in the Study of Religion: Prospects and Limitations - Sztajer, Sławomir (Sensus Historiae, 2024)
The cognitive turn in the study of religion refers to new interdisciplinary research projects developed on the foundation of cognitive science and having increasing influence on the contemporary study of religion. The cognitive science of religion introduces essential theoretical and methodological innovations, emphasizing the role of empirical research, including the experimental method, and drawing on the achievements of natural sciences. Cognitive scientists focus on the cognitive and evolutionary determinants of religious ideas and behavior. The article discusses the main features, methodological assumptions, and limitations of the cognitive science of religion.